PEMILIHAN UMUM MENURUT UUD 1945 (Argumentasi Antara Pemilihan Umum Serentak dan Pemilihan Umum Tidak Serentak). - Mirza Sahputra, Husni A. Jalil, Iskandar A.Gani (Jurnal Ilmu Hukum, 2015)
Abstract:Article 22 paragraph (2) of the 1945 Constitution on the General Elections states that “The general election is held in order to elect members of the House of Representatives, Regional Legislatives Council, the President and Vice President, and the Regional Representatives Council